Worldviews and Intergenerational Altruism: A Comparison of Turkish People Living in Turkey and Germany - K. Ali Akkemik; Mehmet Bulut; Marcus Dittrich; Koray Göksal; Kristina Leipold; Masao Ogaki (Center for Economic Studies and ifo Institute (CESifo), 2017)
In this paper, we examine and compare the impact of cultural differences on intergenerational altruism in Turkish people living in Turkey and in Germany, using the anthropological concept of worldview. Data were gathered from four surveys: nationwide surveys in Turkey and Germany, an online survey of Turkish people living in Germany, and a survey conducted as an experiment in a mosque attended by Turkish people in Germany. We find striking differences in parenting attitudes between Turkish people living in Turkey and those who live in Germany. Turkish people living in Germany tend to resemble German people in their parenting attitudes. We also find that differences in confidence attached to worldview beliefs, differences in religiosity, and the subjective probabilities attached to worldview beliefs (such as “All humans evolved from another living organism”) between Turkish people living in Turkey and those in Germany have statistically significant explanatory power for these differences in parenting attitudes.
Keywords: Z10; Z12; D64; 330; intergenerational altruism; worldviews; religion; tough love; spoiling love